1993
DOI: 10.2118/93-03-03
|View full text |Cite
|
Sign up to set email alerts
|

Steam Corefloods With Concurrent X-Ray Ct Imaging

Abstract: A series of steam corefloods has been performed utilizing X-ray CT imaging to monitor phase saturations during the floods. A numerical simulator was used to analyze the experimental results. The steamfloods of initially water-filled sand packs were carried out at low enough flow rates that capillary pressure was comparable in magnitude with viscous pressure drop. Numerically marching the observed pressure drops provided a significant test of the assumed steam-water capillary relationship. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Results in these and the above studies demonstrate that by not properly accounting for heterogeneity, the effective relative permeability compensates for the real effects of underlying fine-scale heterogeneity and may differ significantly from characteristic relative permeability (Cuthiell et al 1993;Saad et al 1995;Nordtvedt et al 1999). This conclusion is the primary motivator of this study, as it will be demonstrated that effective relative permeability may be a function of flowrate even if the characteristic relative permeability is not.…”
Section: Numerical Investigations Of Coreflooding Experimentsmentioning
confidence: 81%
See 2 more Smart Citations
“…Results in these and the above studies demonstrate that by not properly accounting for heterogeneity, the effective relative permeability compensates for the real effects of underlying fine-scale heterogeneity and may differ significantly from characteristic relative permeability (Cuthiell et al 1993;Saad et al 1995;Nordtvedt et al 1999). This conclusion is the primary motivator of this study, as it will be demonstrated that effective relative permeability may be a function of flowrate even if the characteristic relative permeability is not.…”
Section: Numerical Investigations Of Coreflooding Experimentsmentioning
confidence: 81%
“…Computed Tomography (CT) scanning has been used to show that even rocks appearing to be homogeneous often have substantial sub-core scale heterogeneity (Cuthiell et al 1993;Honarpour et al 1994;Graue 1994; Hamon and Roy 2000). The influence of these heterogeneities is often not trivial.…”
Section: Dependency On Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…To address this limitation, advanced techniques such as medical CT scans and NMR spectroscopy have been employed to complement core ooding experimental results (Cuthiell et al, 1993) (Siavashi et al, 2022). Nevertheless, these techniques do not provide dynamic, high-resolution micron-scale visualization of multiphase ow within core sections during experiments (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Core ooding experiments, a conventional technique, are commonly employed to investigate multiphase ow in realistic porous materials (Cuthiell et al, 1993;Qi et al, 2017). These experiments yield macro-scale data, including pressure variations, uid saturation pro les, and produced uid properties, offering insights into multiphase ow behavior within porous rocks.…”
Section: Introductionmentioning
confidence: 99%